PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Hasdiana, Hasdiana; Hasang, Ismail (Economos : Jurnal Ekonomi dan Bisnis, 2018)
The quality of government financial reports is influenced by the utilization of information technology. Constraints to the application of information technology are related to hardware conditions, software used, updating data, conditions of existing human resources, and limited funds. Another thing that affects the quality of financial statements is the government's internal control system itself. This study aims to determine the factors that influence the quality of local government financial reports. Where the factors that influence are the use of information technology and the government's internal control system. Respondents in this study were the head of the department and the finance department of the regional government of the Parepare City. Data analysis using the SPSS version 21.0 program. The statistical method used to test the hypothesis is linear double regression analysis.